2001
DOI: 10.1051/0004-6361:20000081
|View full text |Cite
|
Sign up to set email alerts
|

Complex resonance absorption structure in the X-ray spectrum of IRAS 13349+2438

Abstract: Abstract. The luminous infrared-loud quasar IRAS 13349+2438 was observed with the XMM-Newton Observatory as part of the Performance Verification program. The spectrum obtained by the Reflection Grating Spectrometer (RGS) exhibits broad (v ∼ 1400 km s −1 FWHM) absorption lines from highly ionized elements including hydrogen-and helium-like carbon, nitrogen, oxygen, and neon, and several iron L-shell ions (Fe xvii-xx). Also shown in the spectrum is the first astrophysical detection of a broad absorption feature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
180
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(206 citation statements)
references
References 25 publications
21
180
2
1
Order By: Relevance
“…Only in the case of Mrk 110 and CTS A08.12 do we see a feature between 15 and 17 Å in absorption that can be associated with the Fe-L UTA (Unresolve Transition Array), which is the characteristic signature of warm absorbers (Sako et al 2001). We tested for the presence of warm absorption related with these sources using PHASE (Krongold et al 2003), but in neither case have we found a satisfactory result that would inprove the model fitting.…”
Section: High-resolution Spectral Featuresmentioning
confidence: 97%
“…Only in the case of Mrk 110 and CTS A08.12 do we see a feature between 15 and 17 Å in absorption that can be associated with the Fe-L UTA (Unresolve Transition Array), which is the characteristic signature of warm absorbers (Sako et al 2001). We tested for the presence of warm absorption related with these sources using PHASE (Krongold et al 2003), but in neither case have we found a satisfactory result that would inprove the model fitting.…”
Section: High-resolution Spectral Featuresmentioning
confidence: 97%
“…For iron, which has a best-fit value 2.5σ below the protosolar ratio, some of the stronger lines are notably weaker in the best-fit model, but the main difference is in the absorption due to the unresolved transition array (UTA between 16 and 17.5 Å, Sako et al 2001;Behar et al 2001), because the many absorption lines result in pseudo-continuum absorption. The spacing of 2.68 Å and 3.18 Å between the points of the spline used to fit the continuum in the range 14−18 Å is wider than the UTA, which has a width of about 1.5 Å.…”
Section: Derived Abundancesmentioning
confidence: 99%
“…Recent XMM-Newton observations of the radio-quiet quasar Mrk 205 might provide the first evidence for a dust-torus in a quasar (Reeves et al 2001). XMM-data of IRAS 13349+2438 suggest column-densities which are consistent with a dusty torus (Sako et al 2001). Observations impose important constraints on the properties of such tori.…”
Section: Introductionmentioning
confidence: 97%